2011
DOI: 10.2337/dc10-1068
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bladder Cancer Among Diabetic Patients Treated With Pioglitazone

Abstract: OBJECTIVESome preclinical in vivo studies and limited human data suggest a possible increased risk of bladder cancer with pioglitazone therapy. This is an interim report of an ongoing cohort study examining the association between pioglitazone therapy and the risk of bladder cancer in patients with diabetes.RESEARCH DESIGN AND METHODSThis study includes 193,099 patients in the Kaiser Permanente Northern California diabetes registry who were ≥40 years of age between 1997 and 2002. Those with prior bladder cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
483
3
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(507 citation statements)
references
References 22 publications
6
483
3
15
Order By: Relevance
“…In addition, pioglitazone was reported to be associated with an increased risk of bladder cancer. 12) There have been several reports addressing the optimal blood sugar target level, and these reports have suggested that maintaining strict blood sugar control results in a smaller risk of microvascular complications. 13,14) However, no study has shown definitively that intensive lowering of blood glucose reduces the incidence of macrovascular complications such as myocardial infarction or stroke.…”
mentioning
confidence: 99%
“…In addition, pioglitazone was reported to be associated with an increased risk of bladder cancer. 12) There have been several reports addressing the optimal blood sugar target level, and these reports have suggested that maintaining strict blood sugar control results in a smaller risk of microvascular complications. 13,14) However, no study has shown definitively that intensive lowering of blood glucose reduces the incidence of macrovascular complications such as myocardial infarction or stroke.…”
mentioning
confidence: 99%
“…Both these drugs do not accumulate in patients with CKD, but they can cause edema and heart failure (16). Hence their use is best avoided in CKD patients.…”
Section: Oral Antidiabetic Agents In Ckd (Table 1)mentioning
confidence: 99%
“…These recommendations stem from the fear generated by phenformin (the fi rst drug of this same class) induced lactic acidosis (16).…”
Section: Metforminmentioning
confidence: 99%
“…4 As a result of the findings in rats, the FDA requested a 10-year study of pioglitazone in humans to assess safety with regard to bladder cancer. 5 The 8-year data have been published online 6 and the 10-year results recently were made public. 2 The main results of this study fail to show any association between pioglitazone and risk of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%